Effects of Supervised Strength Training on Physical Fitness in Children and Adolescents: A Systematic Review and Meta-Analysis - José M. Moreno-Torres; Juan Alfonso García-Roca; Oriol Abellan-Aynes; Alvaro Diaz-Aroca (Journal of Functional Morphology and Kinesiology, 2025)
Objective: Strength training has gained recognition as an effective method to enhance physical fitness in children and adolescents. Its benefits include improvements in muscular strength, aerobic capacity (VO2max), and motor performance. However, the diversity in training protocols and participant characteristics across studies necessitates a comprehensive synthesis of the evidence. The aim of this paper was to analyse the influence of a strength training programme in young people aged 6 to 16 years on different aspects of physical fitness. Methods: A search was carried out in the EBSCO, Web of Sciences, and Scopus databases. A total of 634 articles were reviewed, and 22 were finally included in the meta-analysis of articles published between 2013 and 2023 in English or Spanish. Twenty-two studies met the inclusion criteria and were assessed using the AXIS and PEDro tools. Standardised mean differences (SMD) and 95% confidence intervals (CI) were calculated. The variables that were most frequently repeated as criteria for evaluating the effectiveness of strength training were the following: (1) strength of the lower/upper body muscles; (2) VO2max; (3) sprint performance. Results: Strength training interventions produced statistically significant improvements in all analysed variables. Most effective programmes lasted between 6 and 12 weeks, with 2–3 sessions per week. VO2max showed the greatest improvement, followed by upper and lower limb strength, and sprint performance. Heterogeneity ranged from low to moderate. Conclusions: Supervised strength training programmes can significantly enhance physical fitness in school-aged children and adolescents. While the included studies varied in design and duration, measurable improvements were commonly observed in interventions lasting at least 6–8 weeks. Future research should explore age- and maturity-related responses through subgroup analyses. Limitations include the exclusion of studies published after 2023 and the wide age range of participants without biological stratification.